2022
DOI: 10.1111/os.13204
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Function of miRNA in Intervertebral Disc Degeneration

Abstract: Intervertebral disc degeneration (IDD) disease has been considered as the main cause of low back pain (LBP), which is a very common symptom and the leading cause of disability worldwide today. The pathological mechanism of IDD remains quite complicated, and genetic, developmental, biochemical, and biomechanical factors all contribute to the development of the disease. There exists no effective, non-surgical treatment for IDD nowadays, which is largely related to the lack of knowledge of the specific mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Biological processes showed that IDD was closely bound up with regulation of inflammatory response, positive regulation of cytokine production, endogenous cell promotion and other items. A number of current studies have shown that various genes can regulate the proliferation and apoptosis of intervertebral disc cells, or promote and inhibit the release of inflammatory factors to regulate the development of IDD [4]. The cell composition involved cell substrate junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological processes showed that IDD was closely bound up with regulation of inflammatory response, positive regulation of cytokine production, endogenous cell promotion and other items. A number of current studies have shown that various genes can regulate the proliferation and apoptosis of intervertebral disc cells, or promote and inhibit the release of inflammatory factors to regulate the development of IDD [4]. The cell composition involved cell substrate junction.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can bind to target mRNAs to destabilize them and inhibit mRNAs translation or cause their degradation, thus achieving post-transcriptional regulation of gene expression. MiRNAs play an important role in the biological process of IDD and participate in it by regulating inflammatory response, cell proliferation, cell apoptosis and other pathways [4,5]. Dong found that miR-640 inhibited the expression of β-catenin and EP300, thereby suppressing WNT signalling and inducing nucleus pulposus cell degeneration [6].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction and abnormal expression of inflammatory factors can disrupt the balance of ECM metabolism, cause inflammation, and accelerate IVDD. Tumor necrosis factor (TNFα), interleukins (IL), nitric oxide, and prostaglandin E2 (PGE 2 ) are the main factors for the inflammatory reaction in IVD [ 29 ]. Cytokines initiate the inflammatory cascade by stimulating a range of pathogenic responses in the disc cells that could promote autophagy, senescence, and apoptosis.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…There exists no effective, surgical or non-surgical treatment for IVDD nowadays, which is largely related to the lack of knowledge of the specific mechanisms of IVDD, and the lack of effective specific therapeutic targets [ 29 ].…”
Section: Treatments For Ivddmentioning
confidence: 99%
“…MiRNAs play an important role in the occurrence and development of tendon injuries, osteoarthritis, rheumatoid arthritis, IDD, and other diseases [ 11 13 ]. Although some studies have reported the role of miRNAs in IDD [ 14 , 15 ], scientific econometric analysis in this field has not been reported.…”
Section: Introductionmentioning
confidence: 99%